Fuelwood Comparison with Other Kinds of Fuel (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
A part of Latvia’s forest resources, namely, branches, stumps, small stump top ends, firewood, slabs, sawdust, etc. remains unutilised both in the felling sites and woodworking plants. All this can be successfully utilised for production of heat energy, thereby replacing a part of the imported natural gas, coal and liquid fuel. To assess the utilisation of a definite type of primary energy, not only its accessibility and costs, but also calorific value should be known. The rational utilisation of energy resources in Latvia is urgent, since less than 30% from the consumption is obtained in this country. Thus, in 2000, the Latvia’s energy balance showed the total consumption of different types of primary energy resources to be 159 145 TJ (T = 1012). Utilising firewood, woodworking waste and chips, 34 250 TJ of energy was produced, or 21.5 % from the total primary energy consumed in Latvia. In the present study, fuel wood is compared with other types of fuel. If the equivalent value of one ton of coal (tce) is 29.308 MJ/kg, then the calorific value of natural gas and dry wood is 1.507 and 0.644, respectively. If 18.883 MJ of heat is obtained from 1 kg of oven dry wood, then 1.3 kg of wood with the relative moisture (Wr) content 20% and about 2.0 kg of freshly cut wood are necessary. To replace 1 ton of sawdust pellets or granules, 2.44 steres of birch firewood with the moisture content Wr = 20% or 2.63 steres with Wr = 40% are necessary. The above-mentioned amount of pellets or granules can be replaced by 3.47 steres of spruce firewood with Wr = 20% or 3.76 steres with Wr = 40%. The production of 1 kWh of heat from natural gas yields 0.224 kg of carbon dioxide, but in the case of fully combusted wood, from 0.35 to 0.4 kg of carbon dioxide.